Aspartate Metabolism Facilitates IL-1β Production in Inflammatory Macrophages - Wang, Hao; Zheng, Xueyue; Liu, Bingnan; Xia, Yaoyao; Xin, Zhongquan; Deng, Baichuan; He, Liuqin; Deng, Jinping; Ren, Wenkai (Frontiers in Immunology, 2021)
Increasing evidence support that cellular amino acid metabolism shapes the fate decision of immune cells; however, whether aspartate metabolism dictates macrophage function is still enigmatic. Here, we found that the metabolites in aspartate metabolism are depleted in lipopolysaccharide (LPS) plus interferon-γ (IFN-γ)-stimulated macrophages. Aspartate promotes interleukin (IL)-1β secretion in M1 macrophages. Mechanistically, aspartate boosts the activation of hypoxia-inducible factor (HIF)-1α and inflammasome, as well as increases the levels of metabolites in aspartate metabolism, like asparagine. Interestingly, asparagine also accelerates the activation of cellular signaling pathways and promotes the production of inflammatory cytokines from macrophages. Moreover, aspartate supplementation augments the macrophage-mediated inflammatory responses in mice and piglets. These results uncover a previously uncharacterized role for aspartate metabolism in directing M1 macrophage polarization.